Complications After Deep Brain Stimulation: A 21-Year Experience in 426 Patients - Jung, In-Ho; Chang, Kyung Won; Park, So Hee; Chang, Won Seok; Jung, Hyun Ho; Chang, Jin Woo (Frontiers in Aging Neuroscience, 2022)
Background: Deep brain stimulation is an established treatment for movement disorders such as Parkinson’s disease, essential tremor, and dystonia. However, various complications that occur after deep brain stimulation are a major concern for patients and neurosurgeons. Objective: This study aimed to analyze various complications that occur after deep brain stimulation. Methods: We reviewed the medical records of patients with a movement disorder who underwent bilateral deep brain stimulation between 2000 and 2020. Among them, patients requiring revision surgery were analyzed. Results: A total of 426 patients underwent bilateral deep brain stimulation for a movement disorder. The primary disease was Parkinson's disease in 315 patients, followed by dystonia in 71 patients and essential tremor in 40 patients. Twenty-six (6.1%) patients had complications requiring revision surgery; the most common complication was infection (12 patients, 2.8%). Conclusions: Various complications may occur after deep brain stimulation, and patient prognosis should be improved by reducing complications.